ANALISIS STRATEGI BAURAN PEMASARAN USAHA JASA BOGA PADA KATERING INFOOD21 PONTIANAK - Irabela Irabela; Maria Ulfah; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis observation aimed to describe the marketing strategy of the catering service business that was applied and to describe the effectiveness of the marketing strategy applied by Catering Infood21 Pontianak on the sale of food products and the income earned. The research method was descriptive qualitative. Aspects of the 4P marketing mix namely product (product), price (price), people (people) and promotion (promotion) were aspects that will be analyzed in this study. In this study the method used by using a descriptive qualitative approach. Based on the results of observations and interviews conducted by researchers in the research process, researchers obtained the information needed in answering the formulation of research problems to achieve the achievement of research objectives that had been previously designed. Meanwhile, based on information management carried out by researchers using the research method contained in it showed that in general the marketing strategy applied by Infood21 Catering is good with a good level of effectiveness, this was indicated by a significant increase, reaching 50 to 60 percent every month compared to before marketing strategy implementedKeyword : Analysis, Marketing Strategy, Catering Service Business